PENGARUH PERTUMBUHAN EKONOMI DAN UPAH MINIMUM TERHADAP KEMISKINAN di JOMBANG JAWA TIMUR - Aris Dwi Septian; Asyarurahim (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
This study aims to analyze: 1) the rate of economic growth and minimum wage in Jombang Regency; 2) the development of poverty in Jombang Regency; 3) the effect of economic growth and minimum wage on poverty in Jombang Regency. The data used in this study are secondary data for the period 2015 - 2022. Data analysis tools using multiple linear regression methods. Based on the results of the analysis, it is known that: 1) The average economic growth of Jombang Regency in the 2015-2022 period was -49%, the growth of the minimum wage of Jombang Regency was 7% and the growth of the poor population was -2% percent; 2) simultaneously economic growth and minimum wages have a significant effect on poverty in Jombang Regency, while partially the variable that has a significant effect on poverty is Economic Growth